Desmodium adscendens (Sw.) DC.: A magnificent plant with biological and pharmacological properties. Issue 4 (27th July 2022) - Manzione, Maria Giulia; Herrera‐Bravo, Jesús; Sharifi‐Rad, Javad; Kregiel, Dorota; Sevindik, Mustafa; Sevindik, Emre; Salamoglu, Zeliha; Zam, Wissam; Vitalini, Sara; Hano, Christophe; Kukula‐Koch, Wirginia; Koch, Wojciech; et al.
Abstract: Desmodium adscendens (Sw.) DC. is a plant of the Fabaceae family especially rich in flavonoids but also in alkaloids, terpenoids, steroids, phenols, phenylpropanoids, glycosides, and volatiles. This herb has been traditionally used in numerous countries all over the world for its pharmacological and biological properties (i.e., it has been used for the treatment of diarrheas, fever, epilepsy, asthma, leishmaniasis, gastroduodenal ulcer, diabetes, hepatic diseases, etc.). Given the wide uses of D. adscendens, this review summarizes all recent data on D. adscendens evaluating its phytochemistry as well as its ethno‐traditional and pharmacological properties. In addition, an association between the phytocompounds of this plant and its potential mechanism of action in cell and animal models has been investigated, focusing with a special emphasis on human experiments. Graphical Abstract: Main biological and pharmacological properties of Desmodium adscendens